Sporepolinic morphology of fluvial terrace sediments in the Western Amazon - Silva, Mayra Nina Araujo; Absy, Maria Lúcia; Latrubesse, Edgardo M.; Albuquerque, Patricia Maia Correia de (Acta Botanica Brasilica, 2020)
Morphological descriptions were made for pollen grains and spores extracted from samples from three sedimentary sections - Chandless 1, Purus 10 and Purus 30 - from fluvial terraces on the Chandless and Purus rivers, Acre State, Brazil. Level CH1-12 at Chandless 1 was C14-dated to 4861 - 5050 cal yr BP, P10-3 of Purus 10 was dated through the OSL method at 8200 +/- 65 yr BP, while P30-6 at Purus 30 was C14 dated to 7845 - 7998 cal yr BP. For pollen analysis, 2 cm3 of each sample was removed, treated with potassium hydroxide (KOH) and acetolysed, followed by palymorph separation with bromoform/alcohol density 2.0 solution. A total of 49 palynomorphs were morphologically described (39 pollen types and 10 Pteridophyte spores). The most frequent pollen types belonged to Anacardiaceae, Arecaceae, Euphorbiaceae, Fabaceae, Rutaceae and Amaranthaceae, while the most frequent spores belonged to Polypodiaceae and Pteridaceae. The pollen richness found in the studied samples reflects the current vegetation occupying the banks of the rivers.
Keywords: Acre; Amazon; Chandless; Palynomorphs; Purus